Maximum Power Point Tracker for Photovoltaic Systems Based on Moth-Flame Optimization Considering Partial Shading Conditions - R. Aghaie; M. Farshad (Journal of Operation and Automation in Power Engineering, 2019)
The performance of photovoltaic (PV) systems is highly dependent on environmental conditions. Due to probable changes in environmental conditions, the real-time control of PV systems is essential for exploiting their maximum possible power. This paper proposes a new method to track the maximum power point of PV systems using the moth-flame optimization algorithm. In this method, the PV DC-DC converter’s duty cycle is considered as the optimization parameter, and the delivered power of the PV system is maximized in real time. In the proposed approach, some schemes are also employed for detecting condition changes and ignoring small fluctuations of the duty cycle. The results of performance evaluation confirm that the proposed method is very fast, robust, and accurate in different conditions such as standard irradiance and temperature, irradiance and temperature variations, and partial shading conditions. The obtained steady-state efficiency and response time for the introduced method under the standard conditions of the test PV system are 99.68% and 0.021 s, respectively. Indeed, in addition to a relatively good efficiency, the faster response of the introduced tracker is also evident in comparison with other methods.